Utilizing Digital Applications as Educational Media for Adolescent Reproductive Health Within The Family Nursing Approach - Nurhaeni, Ani; Rahayu, Rosalia; Oktiany, Thia; Purbaningsih, Endah Sari; Wahyuni, Lili; Marisa, Dewi Erna (Poltekkes Kemenkes Palu, 2025)
Background: Adolescent reproductive health remains a major public health concern, particularly in developing regions. This study aimed to evaluate a digital, family-centered reproductive health education intervention to improve adolescents’ knowledge, attitudes, and family involvement. Methods: A quasi-experimental pretest-posttest control group design was conducted in Cirebon, Indonesia, involving 120 adolescents. Variables included knowledge, attitudes, and family involvement. Instruments were validated questionnaires. Data were analyzed using descriptive statistics, paired t-tests, ANCOVA, and multiple linear regression. Effect sizes were reported using Cohen’s d and η². Results: The intervention group (62.5% female, mean age 15.8 ± 1.2 years) showed significant improvements: knowledge (ΔM = +12.4, p < 0.001, d = 1.45), attitude (ΔM = +9.2, p < 0.001, d = 1.32), and family involvement (ΔM = +14.2, p < 0.001, d = 1.61). ANCOVA indicated significant between-group differences (p < 0.001) with large effect sizes (η² = 0.170–0.187). Conclusion: A digital, family-centered education model effectively enhances adolescent reproductive health outcomes and offers a scalable intervention framework.